If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=(2F+7)/(3F-9)
We move all terms to the left:
(F)-((2F+7)/(3F-9))=0
Domain of the equation: (3F-9))!=0We multiply all the terms by the denominator
F∈R
F*(3F-9))-((2F+7)=0
| -6-9k=165 | | -5x2-3x=0 | | 2+21x=50 | | 0.05=1/2^n | | 59=10+7t | | 4u+3-2(-6u-1)=4(u-1) | | -9v-11=-5(v-5) | | 5.6w^2=7w+18 | | 5x+(6−2x)=−(14+2x) | | -7y+5(y+7)=19 | | 11^2x=16 | | 2w+41=91 | | X=y/5+16 | | 6xx=54 | | 22x-5=3(6x-4)+4x+7 | | 15.3+x=22.5 | | F(x)=-x^2-9x+20 | | 8x⁶+215x³-27=0 | | Y=x³+7x-5 | | x-2-x5-x4-23=0 | | 4)4+x)=2(x-8) | | 9=p/3-11 | | 128=x+140 | | 3x−2=46x−4=8 | | -16r+12r=-8 | | Xx+1=1024 | | 2.3x-7=7 | | -x-5x+12=2(12-x) | | 8i+4i-15=9 | | (y=y+16) | | -x-4x+12=2(12-x) | | -3x+10(2x/3)=-11 |